Perancangan Media Pembelajaran Interaktif Pengenalan Bahasa Inggris untuk Pendidikan Anak Usia Dini (PAUD) Berbasis Android - Leni Fitriani; Dini Destiani Siti Fatimah; Sinta Novitasari (Jurnal Algoritma, 2022)
In the current era, early childhood is more influenced by games on the Android layer than other regional games. Information technology can be an intermediary to be able to provide new experiences on Android devices, namely interactive learning media. the hope of this observation is to make interactive learning media applications to introduce foreign languages ​​especially English for PAUD. The problem faced by teachers who teach in PAUD is that English children can easily be imitated by teachers who are not proficient in English, so learning media applications are needed such as pronunciation of numbers in English with audio, or singing, and to make it easier for teachers in teaching English in an interesting and not boring way to children from an early age. This learning application is designed to overcome the negative impact of smartphone use on children and introduce English from an early age as one of the learning materials. This interactive learning media is designed to help children sharpen their memory and increase their focus on learning services. Apart from providing knowledge and learning, it can also provide entertainment for users or children. This interactive learning media provides a clear picture of English from an early age, helps children master the introduction of English from an early age, and makes it easier for children to learn foreign languages, especially this introduction to English. Please understand at an early age. The design of interactive learning media for the introduction of English follows the MDLC methodology for multimedia development which consists of six stages including concept, design, material documentation, application development, testing, and delivery of the final application results using the Luther-Sutopo version. The prototype or purpose of this application is an interactive learning medium to introduce English to early childhood education.